2006
DOI: 10.1093/chemse/bjl011
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of the Olfactory Event-Related Potential Response

Abstract: In experimental practice, odors are commonly applied to only one nostril for recordings of olfactory event-related potentials (OERPs), but the lateralization aspect of the OERP response is unclear regarding both stimulated nostril and cortical topography. The purpose of the present study was to investigate whether stimulated-nostril side affects OERP amplitudes and latencies and whether these potentials indicate lateralization of brain response in healthy, right-handed, young adults. OERPs were recorded from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Repeated measures multivariate analyses of variance (MANOVAs) were performed for each ERP component and each stimulus modality separately by amplitude and latency. The Pz electrode site was analyzed, as this electrode consistently demonstrates reliable OERP responses (Thesen and Murphy, 2002), and in many studies demonstrates larger peak amplitudes than more lateral electrode sites (Morgan et al, 1997, 2010; Murphy et al, 1994b, 2000; Nordin et al, 1999; Olofsson et al, 2006; Thesen and Murphy, 2002). Greenhouse-Geisser corrections were applied to all MANOVAs.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated measures multivariate analyses of variance (MANOVAs) were performed for each ERP component and each stimulus modality separately by amplitude and latency. The Pz electrode site was analyzed, as this electrode consistently demonstrates reliable OERP responses (Thesen and Murphy, 2002), and in many studies demonstrates larger peak amplitudes than more lateral electrode sites (Morgan et al, 1997, 2010; Murphy et al, 1994b, 2000; Nordin et al, 1999; Olofsson et al, 2006; Thesen and Murphy, 2002). Greenhouse-Geisser corrections were applied to all MANOVAs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous olfactory neuroimaging studies have demonstrated a bilateral activation in primary olfactory cortex and greater activation in the right than in the left orbitofrontal cortex172627. Possible explanation for this inconsistency could be related to the experimental model setting in which any retrieval/recognition task of the incoming stimulus was generated.…”
Section: Discussionmentioning
confidence: 99%
“…54 Event-related potential studies of central olfactory processing also do not reveal main effects for right versus left nostril odor presentations. 55, 56 We did not control for menstrual cycle, which could theoretically modulate differential relationships of odor threshold and smell identification to cognitive functioning between males and females. Lastly, we included both patients with schizophrenia and schizoaffective disorder in the study.…”
Section: Smell Identifi Cation Odor Acuitymentioning
confidence: 99%